Atorvastatin Reduces Plasma Levels of Chemokine (CXCL10) in Patients with Crohn's Disease - Grip, Olof; Janciauskiene, Sabina (PLOS ONE, 2009)
Background In Crohn's disease high tissue expression and serum levels of chemokines and their receptors are known to correlate with disease activity. Because statins can reduce chemokine expression in patients with coronary diseases, we wanted to test whether this can be achieved in patients with Crohn's disease. Methodology/Principal Findings We investigated plasma levels of chemokines (CCL2, CCL4, CCL11, CCL13, CCL17, CCL22, CCL26, CXCL8, CXCL10) and endothelial cytokines (sP-selectin, sE-selectin, sICAM-3, thrombomodulin) in ten Crohn's disease patients before and after thirteen weeks' daily treatment with 80 mg atorvastatin. Of the 13 substances investigated, only CXCL10 was found to be significantly reduced (by 34%, p = 0.026) in all of the treated patients. Levels of CXCL10 correlated with C-reactive protein (r = 0.82, p<0.01). Conclusions/Significance CXCL10 is a ligand for the CXCR3 receptor, the activation of which results in the recruitment of T lymphocytes and the perpetuation of mucosal inflammation. Hence the reduction of plasma CXCL10 levels by atorvastatin may represent a candidate for an approach to the treatment of Crohns disease in the future. Trial Registration ClinicalTrials.gov NCT00454545